Highly cross-linked, nanoporous polysulfone/MOFs mixed matrix membranes with excellent resistance to harsh solvents with strong polarity. (9th May 2023) - Wei, Hongxing; Wang, Wenjing; Xie, Xiangyun; Shu, Zhe; Yi, Zhuan; Gao, Congjie
Abstract: We reported a robust solvent-resistant mixed matrix membranes (MMMs) prepared with the FeCl3 catalyzed cross-linking between the main chains of polysulfone in whole membranes. The above cross-linking guided by the FeCl3 catalyst was a typical Friedel-Crafts reaction, which differed from well-explored photo-grafting methods that only caused the surface cross-linking and enabled a moderate resistance to few solvents with low polarity. MOFs crystals in MMMs endowed membranes with high permeability since they significantly reduced the thickness of skin layer before and after cross-linking. Effects of molar ratios of cross-linker to catalyst, cross-linking time, and cross-linking temperature on degrees of cross-linking as well as solvent resistant performance were fully studied. Our results indicated that: (1) Cross-linked polysulfone membranes displaying superior resistances to strongly polar organic solvents like the DMF, NMP and so on were successfully prepared. This result was demonstrated by the stable flux and nanoparticle rejection observed in those organic solvents. (2) The cross-linking displayed an obvious regulation effect on pore size and rejection performance, which were customizable by changing the cross-linking conditions. This work provides a facile while effective method to fabricate robust solvent-resistant polysulfone membranes that can be used in harsh solvents. Graphical abstract: Image 1 Highlights: Highly cross-linked PSf/MOFs mixed matrix membranes are prepared. The effect of cross-linking conditions on solvent resistant performance was fully studied. The cross-linked membrane has good stability in harsh solvents with high polarity. Permselectivity is tunable by controlling the cross-linking condition.